Development of Social Determinants of Health Screening Tool (SDoHST): qualitative validation with stakeholders and patients in South Australia. (2nd January 2023) - Poirier, Brianna Faye; Ribeiro Santiago, Pedro Henrique; Kapellas, Kostas; Jamieson, Lisa; Neadley, Kate Emily; Boyd, Mark
Abstract: Background: It is well-established that social determinants of health contribute to health and well-being. Among the social determinants of health, health-related social needs (HRSNs) are unmet needs that can be identified by the health care system and addressed through referral to community services. Despite the importance of identifying patients with HRSNs, none of the few screening tools for HRSNs available internationally have received a comprehensive psychometric validation. This study aims to conduct a qualitative validation of the Social Determinants of Health Screening Tool (SDoHST). Methods: This study took place at Lyell McEwin Hospital, a major tertiary hospital located in Adelaide, South Australia. Patient ( n  = 5) and stakeholder ( n  = 9) focus groups were conducted face to face, audio recorded, and transcribed verbatim. Inductive content analysis of focus group transcripts was performed to inform tool modifications (e.g. item rewording). Results: The patient focus group recommended the addition of an explanatory paragraph to improve face validity, and highlighted the importance of reliable transport and internet access. The stakeholder focus group recommended using language that carries less stigma to this particular community and incorporating questions surrounding cultural, linguistic, and spiritual needs. The final version of the SDoHST included 12 items (four original items were removed and seven new items were added during the validation process). Conclusion: The SDoHST is the first validated tool to measure social determinants of health (and specifically HRSNs) in Australia, receiving a comprehensive qualitative validation. The instrument is readily available and future studies will further investigate its psychometric properties with quantitative methods. PLAIN LANGUAGE SUMMARY: A brief guide to screening tools for social determinants of health and their validation The importance of social context in contributing to overall health is well-established. Social determinants of health (SDoH) are social and environmental factors such as employment, housing security, financial stability, social isolation, and personal safety, which contribute up to 60% of overall health. In recent years, there has been a paradigm shift in how healthcare systems view health and wellbeing. There is a growing call to intervene in adverse SDoH from within the healthcare system. One such intervention involves screening patients for unmet needs, such as housing or food insecurity, and providing appropriate connections to organizations in the community to assist with their needs. The screening tools implemented in this context are multiple and diverse. Some target only one or two factors while others assess multiple SDoH. However, little is reported about the development of these tools. If a screening tool is not thoroughly developed and validated, it is impossible to know whether the data collected with the tool are appropriate or relevant. This study details the development and validation of a screening tool for unmet social needs by community members and healthcare providers at a major metropolitan hospital in South Australia.